Assessing Academic Burnout Research Trends and Directions: A Bibliometric Overview of Scopus Data (1984-2023) - Rofif, Wahid Fairuzziyad; Maksum, Muh. Nur Rochim; Anshori, Ari; Hidayat, Syamsul; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
This study aims to track the evolution and trajectory of academic burnout research in Scopus-indexed papers. This study uses bibliometric analytic approaches to examine all of the papers indexed in the Academic Burnout database of the Scopus database between 1984 and 2023. Data analysis was done with R/R-Studio and Excel. VOSviewer analysis analyzes the simultaneous occurrence of keywords and document quotes. The author found 755 publications that matched the specified function, subject, and criteria. This research shows an annual growth rate of 11.86%, with the most publications on academics and burnout in 2022. The United States is the country that contributes the most publications with affiliation from Helsingin Yliopisto. Lee, SM, became the most productive writer on the themes of academics and burnout. The bibliometric analysis carried out was limited to Scopus data. Other national and international databases should have been considered in this study. This study offers suggestions for further research and a concise synopsis of the literature available to academic researchers.